2012
DOI: 10.1002/jmri.23698
|View full text |Cite
|
Sign up to set email alerts
|

Role of the apparent diffusion coefficient in the differential diagnosis of gastric wall thickening

Abstract: Purpose: To evaluate the role of the apparent diffusion coefficient (ADC) measurement made using diffusion‐weighted magnetic resonance imaging (DWMRI) in the differential diagnosis of benign and malignant gastric wall thickening. Materials and Methods: Axial T2‐weighted and DWMRI at b 600 and b 1000 s/mm2 gradients were performed in 94 patients (44 patients with gastric malignancy and 50 patients with benign gastric diseases) with gastric wall thickening which was detected by multidetector computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Using MPR and 3D reconstructed images, the diagnostic accuracy of T staging using MDCT has been reported to have increased (12,27,34), and several recent studies have shown an 83% to 91% overall accuracy of T staging by MDCT with MPR images by using the AJCC 7th guidelines as pathologic references 11,35). In addition, several previous studies on gastric MRI have demonstrated the value of DWI in gastric cancers for detecting tumors and obtaining a differential diagnosis of gastric cancers from lymphoma or other benign conditions (36,37). In our study, adding DWI to conventional T 1 -and T 2 -weighted images and dynamic imaging did not significantly increase the diagnostic performance compared with conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Using MPR and 3D reconstructed images, the diagnostic accuracy of T staging using MDCT has been reported to have increased (12,27,34), and several recent studies have shown an 83% to 91% overall accuracy of T staging by MDCT with MPR images by using the AJCC 7th guidelines as pathologic references 11,35). In addition, several previous studies on gastric MRI have demonstrated the value of DWI in gastric cancers for detecting tumors and obtaining a differential diagnosis of gastric cancers from lymphoma or other benign conditions (36,37). In our study, adding DWI to conventional T 1 -and T 2 -weighted images and dynamic imaging did not significantly increase the diagnostic performance compared with conventional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…129 DWI depends on the mobility of water protons within tissues, which is measured with ADC values and can provide specific information about cellular density of tumors. 102 ADC values help to differentiate between normal gastric wall and pathological tissue, 35,37,48,69,114,130,131 gastric adenocarcinoma and lymphoma, 130 and liver metastases and adjacent liver parenchyma. 35 Furthermore ADC values increase gradually with the degree of histologic tumor differentiation 32,37,132 and there is an inverse correlation between the ADC value and the T-and N-stage.…”
Section: Challenges and Future Perspectives In Gastric Cancer Stagingmentioning
confidence: 99%
“…MR imaging with DWI can increase the sensitivity and accuracy in TNM staging of gastric cancer [ 15 , 16 ], especially in T staging [ 17 , 18 ]. In quantitative terms, the ADC values could help to differentiate gastric cancers from normal gastric walls [ 13 – 15 ], gastric malignancies from benign diseases [ 19 ], and gastric adenocarcinoma from lymphoma [ 20 ]. The ADC values also seemed a useful tool to assess locally advanced gastric adenocarcinoma and gastro-oesophageal tumor response to neoadjuvant treatment [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%